Social and political philosophy : contemporary perspectives - Sterba, James P. 1943- (London : Routledge, 2001)
"Social and Political Philosophy: Contemporary Perspectives introduces and explores the central questions of social and political philosophy from opposing perspectives. Each essay has been written by a philosopher at the forefront of the field, advancing the discussion in ways that are interest to professional philosophers and students alike. Traditional perspectives are balanced with new challenges that have emerged. The book concludes with an attempt to respond to and reconcile a number of the arguments presented in the essays." "Social and Political Philosophy: Contemporary Perspectives is a collection that focuses and reinvigorates discussion on the central questions of social and political philosophy."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Social justice; Justice (Philosophy); Social ethics; Political science -- Philosophy; Sociology -- Philosophy